TINGKAT PEMENUHAN INFORMASI PETANI MELALUI RADIO KOMUNITAS - Atika Atika; Djuara P Lubis; Parlaungan Adil Rangkuti (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2017)
The purpose of this study is to analyze the level of meeting the information needs of farmers through community radio and factors related to the level of fulfillment of information needs. This study was designed as a correlational descriptive survey study. The main data is quantitative data with additional qualitative data as a support through interviews to farmers as community members and farmer’s community radio managers. The location of research in Indramayu Regency, West Java, precisely in Majasari Village, District of Sliyeg and Arjasari Village, Patrol Sub-district. The population is the listener of Radio Remaja and Radio Whisnu, with a sample size of 25%. The results showed that the level of fulfillment of information needs of farmers through different community radio results on each radio listener, which is relatively low on the listener Radio Remaja, while the listener Radio Whisnu quite high. The frequency and duration of listening to the radio is a factor related to the level of meeting the information needs through community radio.